2022
DOI: 10.37391/ijbmr.100301
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Voluntary Employee Turnover in Small Construction Companies for Long-term Productivity

Abstract: Voluntary employee turnover has caused considerable damage to small construction businesses, significantly affecting productivity, profitability, and sustainability. Based on job embeddedness theory, this qualitative multiple case study aimed to explore strategies small construction business owners use to reduce voluntary employee turnover. Participants were 4 successful small construction business owners in Virginia who successfully implemented strategies that reduced voluntary employee turnover by 75% over 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 126 publications
(190 reference statements)
1
2
0
Order By: Relevance
“…In supporting the above study, Chagadama et al (2022) recognise that employee accomplishments on social media improve employee engagement. By publicly acknowledging and celebrating employees' achievements on social platforms, businesses can enhance job embedding and reduce voluntary turnover.…”
Section: Discussion Of Findings: Impact Of Recognition On Employee's ...supporting
confidence: 53%
“…In supporting the above study, Chagadama et al (2022) recognise that employee accomplishments on social media improve employee engagement. By publicly acknowledging and celebrating employees' achievements on social platforms, businesses can enhance job embedding and reduce voluntary turnover.…”
Section: Discussion Of Findings: Impact Of Recognition On Employee's ...supporting
confidence: 53%
“…Through the contribution in these programs, construction organization have shown their commitment to and support for the entire welfare of their employee's wellbeing, resulting in enhanced job satisfaction, reduced employee turnover, and elevated levels of productivity. Employees are more invested in producing high-quality outcomes when they have a vested interest in seeing the organization trust and succeed (Chagadama et al, 2022;Ihedigbo et al, 2023).…”
Section: Why Are Compensation and Benefits Important To Construction ...mentioning
confidence: 99%
“…Moreover, the sustainability of fisheries businesses can also be influenced by factors such as employee turnover. A study on small construction businesses found that reducing voluntary employee turnover was critical to reducing business costs and increasing the performance of key business processes [28].…”
Section: Fisheries Business Sustainabilitymentioning
confidence: 99%